FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA REMBANGAN DAIRY FARM DESA KEMUNING LOR KABUPATEN JEMBER - Dani Agung Wicaksono; Ninik Sri Rahayu Wilujeng; Sefri Ton; Mita Ayu Liliyanti; Maznah Habibatul Baizuro (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2023)
This research aims to examine the influence of service quality and product quality on customer satisfaction, both simultaneous and partial influence. The method used in this research is a quantitative research method, which consists of validity testing, reliability testing, multiple linear regression analysis, multiple determination tests, classical assumption testing and hypothesis testing. The number of samples in this study was 88 respondents who were customers of the Rembangan Dairy Farm, where the purposive sampling method was used to determine the sample. The results of the research show that the service quality variable and the product quality variable simultaneously or partially have a significant effect on the Rembangan Dairy Farm customer satisfaction variable. The R2 value is 37.2%, this shows that the service quality variable and product quality variable are simultaneously able to influence changes in the customer satisfaction variable by 37.2%, while the remaining 62.8% is influenced by other variables outside this research model. The product quality variable has the most dominant influence on customer satisfaction, this is shown by the coefficient value of 0.282 which is greater than the coefficient value of the service quality variable which is 0.232.